Chemoprophylaxis for contacts of leprosy patients: A systematic review and meta-analysis - Ferreira, A. P.M. [UNESP]; Fan, W. [UNESP]; Agarwal, A.; Virmond, M. C.L.; Galan, N. G.A.; Almeida, R. A.M.B. [UNESP]; Jorge, E. C. [UNESP]; Rosa, O. S.; ElDib, R. [UNESP] (My University, 2018)
Individuals who are in close association or proximity with leprosy patients have a greater chance of acquiring the disease. However, the effectiveness of chemoprophylaxis in preventing leprosy in contacts of affected patients for optimal disease control remains unclear and a significant public health issue in developing countries such as India, Brazil, and Bangladesh. Electronic searches of Medline, EMBASE, CENTRAL, and LILACS up to October 2017 were conducted to identify eligible studies. Reference lists of potentially eligible studies were reviewed. We included randomized controlled trials (RCTs) comparing chemoprophylaxis with placebo for the prevention of leprosy infection in contacts of affected patients. A pair of reviewers independently screened eligible articles, extracted data, and assessed risk of bias. The GRADE approach was used to rate overall certainty of the evidence. Six RCTs including 52,483 participants proved eligible. Results suggested a statistically significantly reduction in clinical leprosy in contacts both, up to two years (Risk Ratio 2 (RR) 0.32, 95% Confidential Interval (CI) 0.17, 0.62; p < 0.0007; I =70%, p=0.07; low-certainty evidence) and 2 from two to five years of follow-up (RR 0.51, 95% CI 0.29, 0.89; p=0.02; I =80%, p < 0.0005; low-certainty evidence) with the use of chemoprophylaxis in comparison to placebo. However, results suggested a non- 2 significant reduction in clinical leprosy in contacts over five years (RR 0.77, 95% CI 0.46, 1.28; p =0.31; I =48%, p=0.16; low-certainty evidence). Low-certainty evidence shows that chemoprophylaxis is effective in the reduction of clinical leprosy in contacts up to two years and from two to five years. However, due to lowcertainty evidence there is no significant effect of chemoprophylaxis in contacts, over five years follow-up period.
Keywords: Chemoprophylaxis; Grade; Leprosy; Meta-analysis; Systematic review